2010
DOI: 10.5194/acp-10-4611-2010
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and modelling of tropospheric reactive halogen species over the tropical Atlantic Ocean

Abstract: Although tropospheric reactive halogen chemistry is well studied in coastal and polar environments, the presence of halogens over the open ocean environment has not been widely reported. The impacts of halogens on the tropical open ocean marine boundary layer (MBL), in particular, are not well characterised. This paper describes observations of iodine monoxide (IO) and bromine oxide (BrO) over eight months in the tropical open ocean MBL, on the north-eastern side of São Vicente (Cape Verde Islands, 16.85° N, 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
254
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(278 citation statements)
references
References 113 publications
(129 reference statements)
21
254
3
Order By: Relevance
“…Gas-phase BrO was measured by longpath differential optical absorption spectroscopy (LP-DOAS) at CVAO 6,11 and by multiaxis differential optical absorption In the EUROPE scenario the model overestimated the observations of BrO by one or more ppt, while in the other scenarios BrO was generally within the range of the observations, although it tended to increase with time ( Figure 1g); the typical BrO peaks at dawn and dusk were several ppt larger than observed. 11 The model results were in broad agreement with the observations by ref 5, but in contrast with the observations by ref 10, who reported BrO below detection limit upwind of CVAO and very high BrO mixing ratios (up to 10.2 ppt) between Cape Verde and the African coast; however, it is likely that the latter were affected by local emissions not included in the model. Br inorg was generally overestimated by the model (Figure 1h): in the EUROPE scenario, Br inorg was overestimated by about a factor of 2, while in the other scenarios it was overestimated by a factor of 10.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…Gas-phase BrO was measured by longpath differential optical absorption spectroscopy (LP-DOAS) at CVAO 6,11 and by multiaxis differential optical absorption In the EUROPE scenario the model overestimated the observations of BrO by one or more ppt, while in the other scenarios BrO was generally within the range of the observations, although it tended to increase with time ( Figure 1g); the typical BrO peaks at dawn and dusk were several ppt larger than observed. 11 The model results were in broad agreement with the observations by ref 5, but in contrast with the observations by ref 10, who reported BrO below detection limit upwind of CVAO and very high BrO mixing ratios (up to 10.2 ppt) between Cape Verde and the African coast; however, it is likely that the latter were affected by local emissions not included in the model. Br inorg was generally overestimated by the model (Figure 1h): in the EUROPE scenario, Br inorg was overestimated by about a factor of 2, while in the other scenarios it was overestimated by a factor of 10.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…The seasonal changes for both species were within the variability of the dataset. Detailed 1-D modelling of the sources of halogens and their impact on the boundary layer chemistry by Mahajan et al, (2010) indicates that the IO and BrO account for up to 45 % of the observed O 3 destruction at the surface around Cape Verde. In addition, we suggest that an extra iodine source from the surface is necessary and is most probably photolysis dependent , because the observed fluxes of iodocarbons account for only 10-25 % of the observed IO .…”
Section: Halogen Chemistrymentioning
confidence: 99%
“…In 2007, the observatory was host to the RHaMBLe intensive field campaign, during which a number of additional measurements were made to complement the long-term measurements at the site , including LP-DOAS measurements of halogen species (Read et al, 2008;Mahajan et al, 2010a) and formaldehyde (Mahajan et al, 2010b), and LIF-FAGE measurements of OH and HO 2 . The halogen monoxide radicals BrO and IO exhibited a "top-hat" diurnal cycle (Vogt et al, 1999(Vogt et al, , 1996Read et al, 2008;Mahajan et al, 2010a) with essentially zero concentration in the hours of darkness and generally constant values of approximately 2.5 ppt BrO and 1.4 ppt IO during the day.…”
Section: The Cape Verde Atmospheric Observatorymentioning
confidence: 99%
“…Observations of BrO and IO radicals within the MBL have demonstrated widespread impacts on atmospheric composition and chemistry (Alicke et al, 1999;Sander et al, 2003;Leser et al, 2003;Saiz-Lopez and Plane, 2004;SaizLopez et al, 2004SaizLopez et al, , 2006Peters et al, 2005;Whalley et al, 2007;Mahajan et al, 2010a;Commane et al, 2011;Dix et al, 2013;Gomez Martin et al, 2013;Le Breton et al, 2017), including significant effects on HO x concentrations and on the HO 2 : OH ratio in coastal and marine locations (Bloss et al, 2005a(Bloss et al, , 2010Sommariva et al, 2006;Kanaya et al, 2007;Whalley et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation